EFEKTlVlTAS MEDlA PERMAlNAN LUDO TERHADAP PERUBAHAN PENGETAHUAN DAN SlKAP TENTANG KONSUMSI BUAH DAN SAYUR PADA SISWA KELAS IV SDN 92 KOTA JAMBI - Ursin Nafika (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to analyze the effectiveness of the ludo game media in improving knowledge and attitudes regarding fruit and vegetable consumption among fourth-grade students of SDN 92 Jambi City. Fruit and vegetable consumption among elementary school children remains low; therefore, engaging and interactive educational media are needed to enhance understanding and foster positive attitudes toward healthy eating habits. This research employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of all fourth-grade students of SDN 92 Jambi City selected through total sampling technique. Data were collected using questionnaires to measure students’ knowledge and attitudes before and after the educational ludo game intervention. Statistical analysis was conducted to determine differences in scores before and after the treatment. The results showed an increase in students’ knowledge and attitude scores after the intervention. Therefore, the ludo game media was found to be effective in improving knowledge and fostering positive attitudes toward fruit and vegetable consumption. Game-based learning media can serve as an alternative health promotion strategy in elementary school settings.